Controversies about the Secondary Prevention of Spontaneous Preterm Birth - Kyvernitakis, Ioannis; Maul, Holger; Bahlmann, Franz (Geburtshilfe und Frauenheilkunde, 2018)
Preterm birth is one of the major global health problems and part of the Millennium Development goals because of the associated high number of perinatal or neonatal mortality and long-term risks of neurodevelopmental and metabolic diseases. Transvaginal sonography has meanwhile been established as a screening tool for spontaneous preterm birth despite its relatively low sensitivity when considering only the cervical length. Vaginal progesterone has been shown to reduce prematurity rates below 34 weeks in a screening population of singleton pregnancies. Up to now, no positive long-term effect could be demonstrated after 2 years. It seems to have no benefit to prolong pregnancies after a period of preterm contractions and in risk patients without cervical shortening. Meta-analyses still demonstrate conflicting results dependent on quality criteria used for selection. A cerclage is only indicated in singleton pregnancies with previous spontaneous preterm birth and a combined cervical shortening in the current pregnancy. Nevertheless, the short- and long-term outcome has never been evaluated, whereas maternal complications may be increased. There is no evidence for a prophylactic cervical cerclage in twin pregnancies even in cases with cervical shortening. Emergency cerclage remains an indication after individual counseling. The effect of a cervical pessary in singleton pregnancy seems to be more pronounced in studies where a few investigators with increasing experience have treated and followed the patients at risk for preterm birth. Mainly in twin pregnancies, pessary treatment seems to be promising compared to other treatment options of secondary prevention when the therapy is started at early stages of precocious cervical ripening. At present, several international trials with the goal to reduce global rates of prematurity are in progress which will hopefully allow to specify the indications and methods of intervention for certain subgroups. When trials are summarized, prospective meta-analyses carry a lower risk of bias than the meanwhile uncontrolled magnitude of retrospective meta-analyses with conflicting results.
Keywords: preterm birth; cervical shortening; progesterone; cerclage; pessary